Phenoxazine Derivatives Suppress the Infections Caused by Herpes Simplex Virus Type-1 and Herpes Simplex Virus Type-2 Intravaginally Inoculated Into Mice - Kyoko Hayashi; Toshimitsu Hayashi; Keisuke Miyazawa; Akio Tomoda (Elsevier, 2010)
We examined the in vivo antiviral activities of 2-amino-4,4α-dihydro-4α-7-dimethyl-3H-phenoxazine-3-one (Phx-1), 3-amino-1,4α-dihydro-4α-8-dimethyl-2H-phenoxazine-2-one (Phx-2), and 2-aminophenoxazine-3-one (Phx-3) against herpes viruses. The virus yield three days after administration, changes in the 6-degree's lesion scores, and the morbidity were assessed after herpes simplex virus type-1 (HSV-1) [acyclovir (ACV)-sensitive KOS strain or ACV-resistant A4-3 strain] or HSV-2 (ACV-sensitive UW 268 strain) was inoculated intravaginally to mice with administration of Phx-1, Phx-2, Phx-3, or ACV (0.2 mg per administration, 3 times daily) for 8 days starting from 1 day before virus inoculation to 7 days after infection. Phx-1, Phx-2, and Phx-3 extensively suppressed the virus yield of HSV-1. Only Phx-2 exerted moderate inhibitory effects against HSV-2 in mice. The lesion scores, as clinical signs manifested by infection of the KOS strain of HSV-1, were extensively suppressed by intravaginal application of Phx-1, Phx-2, or Phx-3. The lesion scores in HSV-2-infected mice indicated moderate suppression, when Phx-1, Phx-2, or Phx-3 was applied. Without treatment by one of the compounds, none of the HSV-1- infected mice died, but all the HSV-2-infected ones did. However, by the administration of Phx-1, Phx-2, or Phx-3 fairly improved the survival rates of the HSV-2-infected mice. Phx-2 showed dose-dependent anti-HSV-2 efficacy when administered at doses of 0.2 and 1 mg per administration. The present in vivo data suggest that the Phx-1, Phx-2, and Phx-3 are attractive candidates for agents to prevent both replication of HSV and aggravation of lesions caused by these viruses. Keywords:: herpes simplex virus type l, herpes simplex virus type 2, phenoxazine, intravaginal application